Optimization of the Production Parameters of Composites from Sugarcane Bagasse and Iron Salts for Use in Dye Adsorption - Carine Pereira da Silva; Marluce Oliveira da Guarda Souza; Walter Nei Lopes dos Santos; Laiana Oliveira Bastos Silva (The Scientific World Journal)
In this study, mechanical mixtures of sugarcane bagasse and iron salts (nitrate, acetate, or a mixture of both) were subjected to thermal decomposition for producing iron oxide and carbonaceous composite materials, which were evaluated as adsorbents for removing dyes from water using methylene blue (MB) as a model system. Aiming to optimize the conditions for obtaining composite adsorbents, the Box-Behnken design (BBD) was used to study the effects of mass sugarcane bagasse/mass iron salt, type of mixture of sugarcane bagasse/iron salt, and temperature on the response to be obtained (adsorption capacity, qe) before the execution of the adsorption tests. The synthesized composites were characterized by X-ray diffraction (XRD) analysis, scanning electron microscopy (SEM), and Brunauer-Emmett-Teller (BET) surface area analysis. The relationship between the characteristics of different materials, based on the processing of statistical data and the results of the adsorption tests, helped determine the routes that led to formation of composites with the most suitable properties for the removal of MB dye. Different phases, such as magnetite (Fe3O4) and/or maghemite (γ-Fe2O3) and iron carbide (Fe3C), were formed. The composites that presented the highest qe values were SB/IN 1:1 (600°C) and SB/IN-IA 1:2 (400°C). The first, which contained iron carbide (Fe3C), according to the XRD results, also showed larger BET surface area than the other composites. These properties may have contributed to the higher MB adsorption efficiency of this material in aqueous medium. The sample SB/IN-IA 1:2 (400°C) had lower specific area and was composed of magnetite and/or maghemite phases. In this case, the high qe was probably associated with the surface properties promoted by combination with the carbonaceous material, favoring interactions with MB.